Cyclomodulins-harboring Escherichia coli isolated from obese and normal-weight subjects induces intestinal dysplasia in a mouse model - DeLira-Bustillos, Nora; Angulo-Zamudio, Uriel A.; Leon-Sicairos, Nidia; Flores-Villaseñor, Hector; Velazquez-Roman, Jorge; Tapia-Pastrana, Gabriela; Canizales-Quinteros, Samuel; Velázquez-Cruz, Rafael; Cortez-Hernández, Jesús Alberto; Canizalez-Roman, Adrian (World journal of microbiology & biotechnology, 2024)
Recently, cyclomodulins have been identified in Escherichia coli ( E. coli ), which can induce dysplastic damage. This work aimed to determine the dysplastic activity of cyclomodulin-harboring E. coli isolated from CRC patients, obese and normal-weight subjects in a mouse model. Forty-two mice were pretreated with streptomycin, azoxymethane, and dextran sodium sulfate. Mice were infected with E. coli pks + isolated from a CRC patient, with E. coli pks + cif + isolated from obese or normal-weight subjects, or with E. coli HB101. The presence of cyclomodulin-harboring E. coli in the feces, weight loss, changes in fecal consistency, and the presence of blood in the feces were monitored and used to assess the disease activity index (DAI). After 62 days, the mice were sacrificed to evaluate the presence of intestinal polyps and dysplastic damage by histologic sections. Cyclomodulin-harboring E. coli colonized the mice; these mice exhibited weight loss and watery diarrhea, and isolated normal-weight E. coli had a higher DAI. Polyps were observed in mice infected with cyclomodulin-harboring E. coli in the ileum but to a greater extent in obese isolates. E. coli isolated from CRC showed more significant endothelial damage associated with dysplasia in the ileum in equal proportions from obese and normal-weight isolates. In conclusion, E. coli harboring cyclomodulins isolated from CRC, obesity, or normal weight can cause dysplastic damage in the ileum of mice and may be a risk factor for CRC development.